Searching for stable, five-coordinate aquated Al(III) species. Water exchange mechanism and effect of pH - Hanauer, Hans; Puchta, Ralph; Clark, Timothy; van Eldik, Rudi (Inorganic Chemistry, 2007)
Density functional theory calculations have been performed for the water exchange mechanism of aquated Al(III). The effect of pH was considered by studying the exchange processes for [Al(H2O)(6)](3+) and its conjugated base, [Al(H2O)(5)OH](2+). Both complexes were found to exchange water in a dissociative way with activation energies (E-A) of 15.9 and 10.2 kcal/mol, respectively. The influence of solvent molecules on the gas-phase cluster model was considered by the addition of up to four water molecules to the model system. The stabilizing effect of the solvent on the transition state decreases E-A to 8.6 (hexa-aqua complex) and 7.6 (monohydroxo complex) kcal/mol, whereas E-A for all hydroxo species is consistently significantly lower than those for the related aqua systems, which indicates a much faster water exchange rate. For the hydroxo complex, all calculated five-coordinate intermediates, nH(2)O center dot[Al(H2O)(4)(OH)](2+) (n = 1, 2, 3, 4, 5), are more stable than the corresponding six-coordinate reactants. Our results therefore suggest the presence of a stable five-coordinate species of aquated Al(III), namely, the [Al(H2O)(4)(OH)](2+) complex.